The Relationship between Transactional Distance Perceptions and Academic Self-Efficacy - Alanoglu, Muslim; Karabatak, Songul; Karabatak, Murat (Institute of Electrical and Electronics Engineers Inc., 2023)
This study aimed to examine the change in teacher candidates' transactional distance perceptions and academic self-efficacy belief levels over time in the distance education process and the relationship between each other. For this purpose, the study was carried out with a quantitative approach using a repeated measures design. The study group of the research consists of 73 volunteer teacher candidates studying at Firat University in the spring term of 2022-2023. To collect the research data, the Academic Self-Efficacy Scale and Transactional Distance Perception Scale were used. As a result of the study, it was found that the academic self-efficacy beliefs of the teacher candidates and their transactional distance perceptions were sufficient. It was observed that the relationship between academic self-efficacy belief and transactional distance perception increased as teacher candidates' interactions with distance education elements increased over time. Various suggestions were presented at the end of the study. © 2023 IEEE.
11th International Symposium on Digital Forensics and Security, ISDFS 2023 -- 11 May 2023 through 12 May 2023 -- TN -- 189042
Keywords: academic self-efficacy; distance education; transactional distance